Enhanced energy storage performance of polyethersulfone-based dielectric composite via regulating heat treatment and filling phase - Zhang, Yue (2023)
Polyethersulfone (PESU) has distinctive features of great breakdown strength and low dielectric loss. However, some factors limit the practical application of PESU dielectric materials in the field of energy storage, for instance, the low energy storage density, polarization strength and dielectric constant of PESU. In this work, ZnO nano-shell and BFSTO nano-shell coated BZCT are successfully synthesized, respectively, using the hydrothermal method. Compared to the pure PESU and BZCT/PESU, discharged energy density and efficiency are obviously improved by adding the core-shell structural nanofibers (NFs) into the PESU matrix. Particularly, a remarkably suppressed dielectric loss in 2 wt% BZCT@BFSTO/PESU composites with an outstanding dielectric energy density and an excellent charging-discharging efficiency are simultaneously achieved. The results demonstrate that the discharge energy density of the 2 wt% BZCT@BFSTO/PESU can reach 10.5 J/cm3 under the electric field of 500 kV/mm, and the charge-discharge efficiency is 84%. This in-depth research on PESU-based composite dielectrics has laid an experimental and theoretical basis for the improvement of the dielectric properties and energy storage performance of polymer-based composite, resulting in promoting the development of new dielectric capacitors, and paving the way for the applications of it in the field of energy storage.